The Integration Of Five Main Goals Of Shariah In The Production Of Science And Technology For Human Well-being - Mohamad Aniq Aiman Alias; Mohd Rushdan Mohd Jailani; Wan Abdul Fattah Wan Ismail; Ahmad Syukran Baharuddin (Intelligentia Resources, 2024)
Non-Indexed Publication